Bilingualism and intellectual disabilities: linguistic and metalinguistic abilities, in Spanish and in Catalan, of speakers with Prader-Willi syndrome - Garcia-Alcaraz, Estela; M. Liceras, Juana (Revista de Investigación en Logopedia, 2024)
This study investigates the linguistic and metalinguistic abilities of Spanish-Catalan bilinguals with intellectual disabilities due to genetic disorders. Participants were administered both standardized tests and an experimental task. Regarding the latter, adopting Bialystok’s and collaborators metalinguistic cognitive framework, eight bilinguals with Prader-Willi Syndrome were administered, in both Spanish and Catalan, a grammaticality judgment task manipulating grammaticality and semantic plausibility. As a result, the task included sentences involving different levels of linguistic knowledge and executive control abilities. Previous research has evidenced that typically developing bilinguals showed (i) similar results in both their languages in those sentences targeting high executive control demands but low linguistic knowledge abilities (metalinguistic measure) and (ii) better results in the dominant language in those sentences targeting high linguistic knowledge abilities but low executive control demands (linguistic measure). Our results show that participants show comparable linguistic and metalinguistic abilities in both Spanish and Catalan.